2021
DOI: 10.3390/infrastructures6090120
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation for Roads Considering the Addition of Geogrids in Karst Geohazards Zones

Abstract: Design of road infrastructure in karst terrain is a challenge for any geotechnical condition caused by the weathering of the subsoil. Previous investigations pointed out the efficiency of the roads with geogrids, however there are few studies analyzing road reinforced under karst geohazards. This paper presents a numerical study of the geogrid additions in a typical Mexican road and considering 19 cavities in the subsoil due to failures of the roads in these terrains. The rocks and the soil were simulated by H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In a parametric analysis based on 2-D Finite Element modeling by Neves et al [20], which aimed to determine the impact of reinforcing the subgrade using a geogrid in pavement design, it was noted that the number of load cycles increased due to reinforcement, indicating increased pavement life. The application of geogrids in road pavements on karst geohazards zones was analyzed using numerical simulation by Conrado-Palafox et al [21]. It was concluded that embedding the geogrid between the bedrock and the subgrade mitigated the failure effectively.…”
Section: Introductionmentioning
confidence: 99%
“…In a parametric analysis based on 2-D Finite Element modeling by Neves et al [20], which aimed to determine the impact of reinforcing the subgrade using a geogrid in pavement design, it was noted that the number of load cycles increased due to reinforcement, indicating increased pavement life. The application of geogrids in road pavements on karst geohazards zones was analyzed using numerical simulation by Conrado-Palafox et al [21]. It was concluded that embedding the geogrid between the bedrock and the subgrade mitigated the failure effectively.…”
Section: Introductionmentioning
confidence: 99%